High-strength ultraviolet-resistant outdoor cable and preparation method thereof

By combining the modified anti-ultraviolet agent and modified hydrotalcite, high-strength anti-ultraviolet outdoor cables are formed, which solves the problem of weak UV protection ability of existing cable materials, and significantly improves the mechanical strength and anti-aging performance of the cable.

CN119613882APending Publication Date: 2025-03-14JIANGSU ZEFAN CONSTRUCTION ENGINEERING CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411502932.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The existing polyolefin cable materials have weak protection against ultraviolet rays and insufficient anti-aging performance, which leads to outdoor cables being prone to aging, brittleness, cracking and other phenomena under the influence of wind, rain, sun, heat, ozone and other factors, causing physical and mechanical properties to become deteriorated.

Method used

Modified anti-ultraviolet agents are used to participate in the polymerization of styrene to form a stable polybenzene three-dimensional crosslinking structure and mixed with modified hydrotalcite. Through the physical shielding and chemical absorption of modified hydrotalcite, the cable's resistance to UV, anti-aging and high-strength properties are enhanced.

Benefits of technology

It significantly improves the mechanical strength, thermal stability and oxidation resistance of the cable, effectively prevents the damage to the molecular structure by ultraviolet radiation, extends the service life of the cable, and improves safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a high-strength ultraviolet-resistant outdoor cable and a preparation method thereof, and relates to the technical field of cables. According to the invention, 2-hydroxy-5-chlorobenzophenone and vinyltrihydroxysilane react and are combined to prepare a modified anti-ultraviolet agent, so that the strength, thermal stability and oxidation resistance of the cable are remarkably improved, and during ultraviolet radiation, ultraviolet energy is converted into heat energy to be released, so that the anti-ultraviolet performance is improved; the polyphenyl three-dimensional cross-linked structure is formed by polyphenyl, then participates in the polymerization reaction of styrene, the mechanical strength of the cable is remarkably enhanced, and finally, the polyphenyl three-dimensional cross-linked structure is mixed with the modified hydrotalcite, so that the effects of ultraviolet resistance, aging resistance and high strength are achieved. According to the modified hydrotalcite, calcium dobesilate and naphthalene diisocyanate are subjected to an addition reaction, so that the mechanical property of the cable is remarkably improved; then, the calcium element and the hydrotalcite are subjected to anion exchange, the interlayer distance is increased, the physical shielding effect is achieved, meanwhile, the calcium element and anions between the layers can achieve the chemical absorption effect on ultraviolet rays, and therefore the anti-ultraviolet effect is enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of cables, in particular to a high-strength UV-resistant outdoor cable and a preparation method thereof. Background Art

[0002] At present, electric energy has become an indispensable energy source in human life. Transmission lines for transmitting high-power electric energy are usually overhead lines and power cables. Long-distance transmission lines use high-voltage overhead lines. Power cables are more complex in structure and more expensive than overhead lines. However, the insulation distance between power cables is small, they occupy less space, and do not take up space when laid underground. They are safe for personal safety, reliable in power transmission, not easy to pollute the environment, and require less operation and maintenance. The safe operation of power cables and their accessories is the basic guarantee for the safety of the entire power system.

[0003] Usually, wire and cable materials are based on plastic and rubber materials, with additives such as stabilizers, plasticizers, inorganic fillers, additives and lubricants added, and particles prepared by kneading, mixing and extrusion. Among them, plastic materials are mostly polyolefins, but the wire and cable sheaths made of polyolefins have poor stability to light and heat, weak anti-ultraviolet ability, and insufficient anti-aging performance. Especially for outdoor cables, under the influence of factors such as wind and rain, sunlight (ultraviolet rays), heat, and ozone, it is easy to cause macromolecular chain breakage and harmful changes in chemical structure, premature aging, brittleness, cracking and other phenomena, so that its physical and mechanical properties deteriorate and even lose insulation and protective effects, causing certain potential dangers, and bringing great hidden dangers to the safety of life and property of society and people. How to improve the weak anti-ultraviolet ability, insufficient anti-aging performance, and low strength of existing polyolefin cable materials is the key of the present invention. Therefore, a kind of anti-ultraviolet polyolefin cable material and its preparation method are very needed to solve the above problems. Summary of the invention

[0004] The object of the present invention is to provide a high-strength UV-resistant outdoor cable and a preparation method thereof, so as to solve the problems existing in the prior art.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions: a high-strength UV-resistant outdoor cable, which includes a copper core, a polyethylene insulation layer, and a composite modified polyolefin outer protective layer from the inside to the outside.

[0006] Furthermore, the composite modified polyolefin outer protective layer is made of modified polyolefin, modified hydrotalcite, carbon black and flame retardant.

[0007] Furthermore, the modified polyolefin is prepared from a modified anti-ultraviolet agent and styrene.

[0008] Furthermore, the modified anti-ultraviolet agent is prepared from 2-hydroxy-5-chlorobenzophenone and vinyl trihydroxysilane.

[0009] Furthermore, the modified hydrotalcite is prepared from calcium hydroxybenzenesulfonate, naphthalene diisocyanate and hydrotalcite.

[0010] Furthermore, a method for preparing a high-strength UV-resistant outdoor cable comprises the following preparation steps:

[0011] (1) Dissolve 17-53 parts of naphthalene diisocyanate and 1-3 parts of a catalyst in 102-318 parts of acetone, add 14-46 parts of calcium hydroxybenzenesulfonate, heat to 50-60°C for reaction for 7-9 hours, cool to 30°C, add 32-98 parts of hydrotalcite, stir at 200 rpm for 1-2 hours, filter out the solid, wash with deionized water 3 times, and dry at 60-70°C for 6-10 hours to obtain a modified hydrotalcite;

[0012] (2) 8 to 22 parts of vinyl trihydroxysilane and 2 to 4 parts of triethylamine are dissolved in 48 to 132 parts of dichloromethane, 7 to 19 parts of 2-hydroxy-5-chlorobenzophenone are added dropwise under stirring at 150 rpm, reacted at 20 to 30° C. for 10 to 16 hours, 64 to 176 parts of deionized water are added, the organic phase is separated, and concentrated at a vacuum degree of -0.07 MPa and 30° C. for 2 to 6 hours to obtain a modified anti-ultraviolet agent;

[0013] (3) Under a nitrogen atmosphere, 2 to 6 parts of a modified anti-ultraviolet agent and 15 to 37 parts of styrene are dissolved in 75 to 185 parts of toluene, 0.5 to 1.1 parts of potassium persulfate are added, the temperature is raised to 80 to 90° C., and the mixture is stirred at 160 rpm for 2 to 4 hours. The solid is filtered and washed three times with deionized water, and dried at 60 to 70° C. for 6 to 10 hours to obtain a modified polyolefin;

[0014] (4) 48-62 parts of modified polyolefin and 4-6 parts of modified hydrotalcite are mixed uniformly, and the mixture is extruded and granulated at a head temperature of 160-180° C., a screw speed of 180-220 r / min, an extrusion pressure of 8-12 MPa, and a shear rate of 200-240 s -1 , to obtain a composite modified polyolefin;

[0015] (5) 62-74 parts of polyethylene, 3-5 parts of calcium stearate, and 4-6 parts of antioxidant 1035 are mixed evenly, melt-extruded and coated with an oxygen-free copper core at 180-190°C to form a 1.2 mm insulation layer, and then 72-88 parts of a composite modified polyolefin, 1-3 parts of carbon black, and 2-4 parts of a flame retardant are added, melt-extruded and coated with an insulation layer at 170-190°C to form a 2.4 mm outer protective layer, and the temperature is reduced to 30°C at 70°C / min to obtain a high-strength UV-resistant outdoor cable.

[0016] Furthermore, the catalyst in step (1) is any one of dibutyltin dilaurate, N,N-dimethylcyclohexylamine and triethanolamine.

[0017] Furthermore, the dripping rate in step (2) is 3 drops / s.

[0018] Furthermore, the flame retardant in step (5) is a mixture of one or more of ammonium polyphosphate, phosphate ester, talcum powder, melamine, and aluminum hydroxide.

[0019] Furthermore, the cross-sectional area of ​​the oxygen-free copper core in step (5) is 70 mm 2 ; The model of the polyethylene is YJ-110.

[0020] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0021] The invention uses a modified anti-ultraviolet agent to participate in the polymerization reaction of styrene to form a stable polyphenyl three-dimensional cross-linked structure, which significantly enhances the mechanical strength of the cable, and then mixes it with modified hydrotalcite to achieve anti-ultraviolet, anti-aging and high-strength effects.

[0022] First, the modified anti-ultraviolet agent uses the chlorine group in 2-hydroxy-5-chlorobenzophenone to react with the hydroxyl group in vinyl trihydroxysilane to introduce Si-O bonds, which significantly improves the cable strength, thermal stability and antioxidant capacity, effectively prevents the damage of ultraviolet radiation to the molecular structure, and initially achieves an anti-ultraviolet effect. On this basis, when exposed to ultraviolet radiation, the molecules undergo thermal motion, and the internal hydrogen bonds formed by the chelate ring formed by the carbonyl group and hydrogen bond in benzophenone are destroyed, converting the ultraviolet light energy into heat energy and returning to the original state, thereby improving the anti-ultraviolet performance.

[0023] Secondly, the modified hydrotalcite is prepared from calcium hydroxybenzenesulfonate, naphthalene diisocyanate and hydrotalcite; the hydroxyl group in calcium hydroxybenzenesulfonate is reacted with the isocyanate group of naphthalene diisocyanate to form a polyurethane containing naphthalene biphenyl, which greatly increases the thermal decomposition temperature of the resin and significantly improves the mechanical properties of the cable; then, anion exchange is carried out with the hydrotalcite, so that the organic group covers the surface of the hydrotalcite or is inserted between its layers, increasing the interlayer spacing, causing multiple reflections and refractions of ultraviolet rays to achieve a physical shielding effect, and at the same time, the calcium element and anions between the layers can chemically absorb ultraviolet rays, thereby enhancing the anti-ultraviolet effect. DETAILED DESCRIPTION

[0024] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0025] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe in detail the various index testing methods of the high-strength UV-resistant outdoor cables prepared in the following examples are as follows:

[0026] Tensile strength and elongation at break before aging: Take the same length of the embodiment and the comparative example, place the samples at room temperature for 20 hours, observe the appearance of the samples, and test them according to GB / T 2951.

[0027] Tensile strength and elongation at break after aging: Take the same length of the embodiment and the comparative example, use a 6kW xenon lamp for irradiation and spray water at a water pressure of 0.12-0.15MPa, and perform periodic ultraviolet irradiation in a cycle of 120 minutes, of which 18 minutes are for simultaneous water spraying and light irradiation, and the other 102 minutes are for light alone, for a total exposure of 2000 hours. Then, the sample is placed at room temperature for 20 hours, the appearance of the sample is observed to see if there are cracks on the appearance, and the tensile strength and elongation at break are tested with reference to GB / T 2951.

[0028] Example 1

[0029] (1) 17 parts of naphthalene diisocyanate and 1 part of dibutyltin dilaurate were dissolved in 102 parts of acetone, 14 parts of calcium hydroxybenzenesulfonate were added, the temperature was raised to 50°C for reaction for 7 hours, the temperature was lowered to 30°C, 32 parts of hydrotalcite were added, the mixture was stirred at 200 rpm for 1 hour, the solid was filtered, washed with deionized water for 3 times, and dried at 60°C for 6 hours to obtain modified hydrotalcite;

[0030] (2) 8 parts of vinyl trihydroxysilane and 2 parts of triethylamine were dissolved in 48 parts of dichloromethane, and 7 parts of 2-hydroxy-5-chlorobenzophenone were added dropwise at a rate of 3 drops / s under stirring at 150 rpm, and the mixture was reacted at 20° C. for 10 hours. 64 parts of deionized water were added, and the organic phase was separated and concentrated at a vacuum degree of -0.07 MPa and 30° C. for 2 hours to obtain a modified anti-ultraviolet agent;

[0031] (3) Under a nitrogen atmosphere, 2 parts of the modified anti-ultraviolet agent and 15 parts of styrene were dissolved in 75 parts of toluene, 0.5 parts of potassium persulfate were added, the temperature was raised to 80° C., and the mixture was stirred at 160 rpm for 2 h. The solid was filtered and washed with deionized water for 3 times, and dried at 60° C. for 6 h to obtain a modified polyolefin;

[0032] (4) 48 parts of modified polyolefin and 4 parts of modified hydrotalcite were mixed evenly, and then extruded and granulated at a feed head temperature of 160°C, a screw speed of 180 r / min, an extrusion pressure of 8 MPa, and a shear rate of 200 s -1 , to obtain a composite modified polyolefin;

[0033] (5) Mix 62 parts of polyethylene YJ-110, 3 parts of calcium stearate, and 4 parts of antioxidant 1035, melt and extrude at 180°C to coat a cross-sectional area of ​​70 mm 2 An oxygen-free copper core is used to form a 1.2mm insulation layer, and then 72 parts of composite modified polyolefin, 1 part of carbon black, and 2 parts of ammonium polyphosphate are added. The insulation layer is melted and extruded at 170°C to form a 2.4mm outer protective layer. The temperature is lowered to 30°C at 70°C / min to obtain a high-strength UV-resistant outdoor cable.

[0034] Example 2

[0035] (1) 35 parts of naphthalene diisocyanate and 2 parts of N,N-dimethylcyclohexylamine were dissolved in 210 parts of acetone, 30 parts of calcium hydroxybenzenesulfonate were added, the temperature was raised to 55°C for reaction for 7 to 9 hours, the temperature was lowered to 30°C, 65 parts of hydrotalcite were added, the mixture was stirred at 200 rpm for 1.5 hours, the solid was filtered out, washed with deionized water for 3 times, and dried at 65°C for 8 hours to obtain modified hydrotalcite;

[0036] (2) 15 parts of vinyl trihydroxysilane and 3 parts of triethylamine were dissolved in 90 parts of dichloromethane, and 13 parts of 2-hydroxy-5-chlorobenzophenone were added dropwise at a rate of 3 drops / s under stirring at 150 rpm, and the mixture was reacted at 25° C. for 13 hours. 120 parts of deionized water were added, and the organic phase was separated and concentrated at a vacuum degree of -0.07 MPa and 30° C. for 4 hours to obtain a modified anti-ultraviolet agent;

[0037] (3) Under a nitrogen atmosphere, 4 parts of a modified anti-ultraviolet agent and 26 parts of styrene were dissolved in 130 parts of toluene, 0.8 parts of potassium persulfate were added, the temperature was raised to 85° C., and the mixture was stirred at 160 rpm for 5 h. The solid was filtered and washed with deionized water for 3 times, and dried at 65° C. for 8 h to obtain a modified polyolefin;

[0038] (4) 55 parts of modified polyolefin and 5 parts of modified hydrotalcite were mixed evenly, and then extruded and granulated at a feed head temperature of 170°C, a screw speed of 200 r / min, an extrusion pressure of 10 MPa, and a shear rate of 220 s -1 , to obtain a composite modified polyolefin;

[0039] (5) Mix 68 parts of polyethylene YJ-110, 4 parts of calcium stearate, and 5 parts of antioxidant 1035, and melt extrude them at 185°C to coat a cross-sectional area of ​​70 mm 2 An oxygen-free copper core is used to form a 1.2mm insulation layer, and then 80 parts of composite modified polyolefin, 2 parts of carbon black, and 3 parts of phosphate are added. The insulation layer is melted and extruded at 170-190°C to form a 2.4mm outer protective layer. The temperature is lowered to 30°C at 70°C / min to obtain a high-strength UV-resistant outdoor cable.

[0040] Example 3

[0041] (1) Dissolve 53 parts of naphthalene diisocyanate and 3 parts of triethanolamine in 318 parts of acetone, add 46 parts of calcium hydroxybenzenesulfonate, heat to 60°C for reaction for 9 hours, cool to 30°C, add 98 parts of hydrotalcite, stir at 200 rpm for 2 hours, filter out the solid, wash with deionized water 3 times, and dry at 70°C for 10 hours to obtain modified hydrotalcite;

[0042] (2) 22 parts of vinyl trihydroxysilane and 4 parts of triethylamine were dissolved in 132 parts of dichloromethane, and 19 parts of 2-hydroxy-5-chlorobenzophenone were added dropwise at a rate of 3 drops / s under stirring at 150 rpm, and the mixture was reacted at 30° C. for 16 hours. 176 parts of deionized water were added, and the organic phase was separated and concentrated at a vacuum degree of -0.07 MPa and 30° C. for 6 hours to obtain a modified anti-ultraviolet agent;

[0043] (3) Under a nitrogen atmosphere, 6 parts of a modified anti-ultraviolet agent and 37 parts of styrene were dissolved in 185 parts of toluene, 1.1 parts of potassium persulfate were added, the temperature was raised to 90° C., and the mixture was stirred at 160 rpm for 4 h. The solid was filtered and washed with deionized water for 3 times, and dried at 70° C. for 10 h to obtain a modified polyolefin;

[0044] (4) 62 parts of modified polyolefin and 6 parts of modified hydrotalcite were mixed evenly, and then extruded and granulated at a feed head temperature of 180°C, a screw speed of 220 r / min, an extrusion pressure of 12 MPa, and a shear rate of 240 s -1 , to obtain a composite modified polyolefin;

[0045] (5) Mix 74 parts of polyethylene YJ-110, 5 parts of calcium stearate, and 6 parts of antioxidant 1035, melt and extrude at 190°C to coat a cross-sectional area of ​​70 mm 2 An oxygen-free copper core is used to form a 1.2mm insulation layer, and then 88 parts of composite modified polyolefin, 3 parts of carbon black, and 4 parts of aluminum hydroxide are added. The insulation layer is melted and extruded at 190°C to form a 2.4mm outer protective layer. The temperature is lowered to 30°C at 70°C / min to obtain a high-strength UV-resistant outdoor cable.

[0046] Comparative Example 1

[0047] The difference between Comparative Example 1 and Example 2 is that step (1) is different, and step (1) is changed to: 30 parts of calcium hydroxybenzenesulfonate are dissolved in 105 parts of deionized water and 105 parts of ethanol, mixed evenly, 65 parts of hydrotalcite are added, stirred at 200 rpm for 1.5 hours, filtered to obtain the solid, and dried at 65° C. for 8 hours to obtain the modified hydrotalcite. The remaining steps are the same as those in Example 2.

[0048] Comparative Example 2

[0049] The difference between Comparative Example 2 and Example 2 is that step (1) is different, and step (1) is changed to: 35 parts of naphthalene diisocyanate and 2 parts of N,N-dimethylcyclohexylamine are dissolved in 210 parts of acetone, 65 parts of hydrotalcite are added, and the mixture is stirred at 200 rpm for 1.5 hours, the solid is filtered, and dried at 65° C. for 8 hours to obtain the modified hydrotalcite. The remaining steps are the same as those in Example 2.

[0050] Comparative Example 3

[0051] The difference between Comparative Example 3 and Example 2 lies in the difference in step (1). Step (1) is changed to: 35 parts of naphthalene diisocyanate and 2 parts of N,N-dimethylcyclohexylamine are dissolved in 210 parts of acetone, 30 parts of calcium hydroxybenzenesulfonate are added, the temperature is raised to 55°C for reaction for 7 to 9 hours, and the mixture is concentrated at a vacuum degree of -0.07 MPa and 30°C for 4 hours to obtain a modified polyurethane; step (4) is changed to: 55 parts of modified polyolefin and 5 parts of modified polyurethane are mixed uniformly, and the mixture is extruded and granulated at a head temperature of 170°C, a screw speed of 200 r / min, an extrusion pressure of 10 MPa, and a shear rate of 220 s -1 The remaining steps are the same as those in Example 2.

[0052] Comparative Example 4

[0053] The difference between Comparative Example 4 and Example 2 is that step (2) is omitted, and step (3) is changed to: in a nitrogen atmosphere, 4 parts of vinyl trihydroxysilane and 26 parts of styrene are dissolved in 130 parts of toluene, 0.8 parts of potassium persulfate are added, the temperature is raised to 85° C., and the mixture is stirred at 160 rpm for 5 hours, the solid is filtered, washed with deionized water for 3 times, and dried at 65° C. for 8 hours to obtain a modified polyolefin. The remaining steps are the same as those in Example 2.

[0054] Comparative Example 5

[0055] The difference between Comparative Example 5 and Example 2 is that there is no step (2), and step (3) is changed to: under a nitrogen atmosphere, 4 parts of 2-hydroxy-5-chlorobenzophenone and 26 parts of styrene are dissolved in 130 parts of toluene, 0.8 parts of potassium persulfate are added, the temperature is raised to 85° C., and the reaction is carried out under stirring at 160 rpm for 5 hours, and the solid is filtered, washed with deionized water 3 times, and dried at 65° C. for 8 hours to obtain a modified polyolefin. The remaining steps are the same as those in Example 2.

[0056] Comparative Example 6

[0057] The difference between Comparative Example 6 and Example 2 is that step (3) is different. Step (3) is changed to: under a nitrogen atmosphere, 26 parts of styrene are dissolved in 130 parts of toluene, 0.8 parts of potassium persulfate are added, the temperature is raised to 85°C, and the reaction is carried out under stirring at 160rpm for 5 hours. The solid is filtered and washed with deionized water 3 times, and dried at 65°C for 8 hours to obtain a modified polyolefin; step (4) is changed to: 55 parts of modified polyolefin, 5 parts of modified hydrotalcite, and 6 parts of modified anti-ultraviolet agent are mixed uniformly, and the mixture is extruded and granulated. The head temperature is 170°C, the screw speed is 200r / min, the extrusion pressure is 10MPa, and the shear rate is 220s. -1 The remaining steps are the same as those in Example 2.

[0058] Effect example

[0059] Table 1 below shows the performance analysis results of high-strength UV-resistant outdoor cables using Examples 1 to 3 of the present invention and Comparative Examples 1 to 6.

[0060] Table 1

[0061]

[0062] From the comparison of the experimental data of Examples 1, 2, and 3 with Comparative Example 1, it can be found that the addition reaction of naphthalene diisocyanate is used to form a polyurethane containing a naphthalene structure, which greatly increases the thermal decomposition temperature of the cable and significantly improves the mechanical properties of the cable; from the comparison of the experimental data of Examples 1, 2, and 3 with Comparative Example 2, it can be found that the anions in calcium hydroxysulfonate can be exchanged with the anions of hydrotalcite, so that the organic groups are covered on the surface of the hydrotalcite or inserted between its layers, increasing the interlayer spacing, and at the same time, the calcium elements and anions therein can chemically absorb ultraviolet rays, thereby achieving an anti-ultraviolet effect; from the comparison of the experimental data of Examples 1, 2, and 3 with Comparative Example 3, it can be found that hydrotalcite has a unique layered structure and ion exchange capacity, has good barrier properties for oxygen, can reflect and refract ultraviolet rays multiple times to achieve a physical shielding effect, and at the same time, the metal elements and anions between the layers can absorb ultraviolet rays. The line plays a role of chemical absorption, thereby enhancing the anti-ultraviolet aging performance of the cable; from the comparison of the experimental data of Examples 1, 2, and 3 with Comparative Example 4, it can be found that when ultraviolet rays are irradiated, the molecules undergo thermal motion, and the internal hydrogen bonds formed by the carbonyl group and the hydrogen bond in 2-hydroxy-5-chlorobenzophenone are destroyed, and the ultraviolet light energy is converted into heat energy and released and returns to the original state, thereby improving the anti-ultraviolet performance; from the comparison of the experimental data of Examples 1, 2, and 3 with Comparative Example 5, it can be found that the Si-O bond is successfully introduced through vinyl trihydroxysilane, which significantly improves the strength, thermal stability and antioxidant ability of the cable, effectively prevents the damage of ultraviolet radiation to the molecular structure, thereby achieving the anti-ultraviolet effect; from the comparison of the experimental data of Examples 1, 2, and 3 with Comparative Example 6, it can be found that the modified anti-ultraviolet agent participates in the polymerization reaction of styrene to form a stable three-dimensional cross-linked structure of polyphenylene, which significantly enhances the mechanical strength of the cable.

[0063] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.

Claims

1. A high-strength UV-resistant outdoor cable, characterized in that: The high-strength UV-resistant outdoor cable comprises a copper core, a polyethylene insulation layer, and a composite modified polyolefin outer protective layer from the inside to the outside.

2. A high-strength UV-resistant outdoor cable according to claim 1, characterized in that: The composite modified polyolefin outer protective layer is made of modified polyolefin, modified hydrotalcite, carbon black and flame retardant.

3. A high-strength UV-resistant outdoor cable according to claim 2, characterized in that: The modified polyolefin is prepared from a modified anti-ultraviolet agent and styrene.

4. A high-strength UV-resistant outdoor cable according to claim 3, characterized in that: The modified anti-ultraviolet agent is prepared from 2-hydroxy-5-chlorobenzophenone and vinyl trihydroxysilane.

5. A high-strength UV-resistant outdoor cable according to claim 2, characterized in that: The modified hydrotalcite is prepared from calcium hydroxybenzenesulfonate, naphthalene diisocyanate and hydrotalcite.

6. A method for preparing a high-strength UV-resistant outdoor cable, characterized in that: The method comprises the following preparation steps: (1) Dissolve 17-53 parts of naphthalene diisocyanate and 1-3 parts of a catalyst in 102-318 parts of acetone, add 14-46 parts of calcium hydroxybenzenesulfonate, heat to 50-60°C for reaction for 7-9 hours, cool to 30°C, add 32-98 parts of hydrotalcite, stir at 200 rpm for 1-2 hours, filter out the solid, wash with deionized water 3 times, and dry at 60-70°C for 6-10 hours to obtain a modified hydrotalcite; (2) 8 to 22 parts of vinyl trihydroxysilane and 2 to 4 parts of triethylamine are dissolved in 48 to 132 parts of dichloromethane, 7 to 19 parts of 2-hydroxy-5-chlorobenzophenone are added dropwise under stirring at 150 rpm, reacted at 20 to 30° C. for 10 to 16 hours, 64 to 176 parts of deionized water are added, the organic phase is separated, and concentrated at a vacuum degree of -0.07 MPa and 30° C. for 2 to 6 hours to obtain a modified anti-ultraviolet agent; (3) Under a nitrogen atmosphere, 2 to 6 parts of a modified anti-ultraviolet agent and 15 to 37 parts of styrene are dissolved in 75 to 185 parts of toluene, 0.5 to 1.1 parts of potassium persulfate are added, the temperature is raised to 80 to 90° C., and the mixture is stirred at 160 rpm for 2 to 4 hours. The solid is filtered and washed three times with deionized water, and dried at 60 to 70° C. for 6 to 10 hours to obtain a modified polyolefin; (4) 48-62 parts of modified polyolefin and 4-6 parts of modified hydrotalcite are mixed uniformly, and the mixture is extruded and granulated at a head temperature of 160-180° C., a screw speed of 180-220 r / min, an extrusion pressure of 8-12 MPa, and a shear rate of 200-240 s -1 , to obtain a composite modified polyolefin; (5) 62-74 parts of polyethylene, 3-5 parts of calcium stearate, and 4-6 parts of antioxidant 1035 are mixed evenly, melt-extruded and coated with an oxygen-free copper core at 180-190°C to form a 1.2 mm insulation layer, and then 72-88 parts of a composite modified polyolefin, 1-3 parts of carbon black, and 2-4 parts of a flame retardant are added, melt-extruded and coated with an insulation layer at 170-190°C to form a 2.4 mm outer protective layer, and the temperature is reduced to 30°C at 70°C / min to obtain a high-strength UV-resistant outdoor cable.

7. The method for preparing a high-strength UV-resistant outdoor cable according to claim 6, characterized in that: The catalyst in step (1) is any one of dibutyltin dilaurate, N,N-dimethylcyclohexylamine and triethanolamine.

8. The method for preparing a high-strength UV-resistant outdoor cable according to claim 6, characterized in that: The dripping rate in step (2) is 3 drops / s.

9. The method for preparing a high-strength UV-resistant outdoor cable according to claim 6, characterized in that: The flame retardant in step (5) is a mixture of one or more of ammonium polyphosphate, phosphate ester, talcum powder, melamine, and aluminum hydroxide.

10. The method for preparing a high-strength UV-resistant outdoor cable according to claim 6, characterized in that: The cross-sectional area of ​​the oxygen-free copper core in step (5) is 70 mm 2 ; The model of the polyethylene is YJ-110.